Big Five personality traits, job satisfaction and subjective wellbeing in China. (December 2013) - Zhai, Qingguo; Willis, Mike; O'Shea, Bob; Zhai, Yubo; Yang, Yuwen
<x xml:space="preserve">Abstract</x> This paper examines the effect of the Big Five personality traits on job satisfaction and subjective wellbeing (SWB). The paper also examines the mediating role of job satisfaction on the Big Five–SWB relationship. Data were collected from a sample of 818 urban employees from five Chinese cities: Harbin, Changchun, Shenyang, Dalian, and Fushun. All the study variables were measured with well‐established multi‐item scales that have been validated both in English‐speaking populations and in China. The study found only extraversion to have an effect on job satisfaction, suggesting that there could be cultural difference in the relationships between the Big Five and job satisfaction in China and in the West. The study found that three factors in the Big Five—extraversion, conscientiousness, and neuroticism—have an effect on SWB. This finding is similar to findings in the West, suggesting convergence in the relationship between the Big Five and SWB in different cultural contexts. The research found that only the relationship between extraversion and SWB is partially mediated by job satisfaction, implying that the effect of the Big Five on SWB is mainly direct, rather than indirect via job satisfaction. The study also found that extraversion was the strongest predictor of both job satisfaction and SWB. This finding implies that extraversion could be more important than other factors in the Big Five in predicting job satisfaction and SWB in a "high collectivism" and "high power distance" country such as China. The research findings are discussed in the Chinese cultural context. The study also offers suggestions on the directions for future research.